Bysmatrum gen. nov. (Dinophyceae)and three new combinations for benthic scrippsielloid species - Faust, M.A.; Steidinger, K.A.
A new generic name is proposed, Bysmatrum gen. nov., for three Scrippsiella species: B. subsalsum comb. nov., B. arenicola comb. nov., and B. caponii comb. nov. These three benthic marine species share a number of morphological characteristics: apical plate l' is wide, asymmetric, and pentagonal and ends at the anterior margin of the cingulum; intercalary plates 2a and 3a are separated by apical plate 3' and 4"; the apical pore complex is a recessed chamber with a large Po plate, elongated X plate, and a raised dome at the center; six cingular plates and four sulcal plates are present; and the thecal surface is vermiculate to reticulate. In contrast, other scrippsielloid species are planktonic, and their morphology differs from the three Bysmatrum species.